2022
DOI: 10.3390/biomedicines10071756
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Polyamines Catabolism in the Crosstalk between Neurons and Astrocytes in Neurodegeneration

Abstract: In mammalian cells, the content of polyamines is tightly regulated. Polyamines, including spermine, spermidine and putrescine, are involved in many cellular processes. Spermine oxidase specifically oxidizes spermine, and its deregulated activity has been reported to be linked to brain pathologies involving neuron damage. Spermine is a neuromodulator of a number of ionotropic glutamate receptors and types of ion channels. In this respect, the Dach-SMOX mouse model overexpressing spermine oxidase in the neocorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 191 publications
(316 reference statements)
0
17
0
Order By: Relevance
“…Recent research, however, has revealed that astrocytes also have significant effects on the neuronal microenvironment through mechanisms like glucose metabolism control, neurotransmitter absorption, synaptic growth and maturation, and the BBB. Notably, gliotransmission—the process by which astrocytes alter neuronal and synaptic function by releasing neuroactive chemicals like glutamate, ATP, and GABA [ 95 ]—was discovered to be the mechanism by which astrocytes act.…”
Section: Astrocyte–neuron Interactionsmentioning
confidence: 99%
“…Recent research, however, has revealed that astrocytes also have significant effects on the neuronal microenvironment through mechanisms like glucose metabolism control, neurotransmitter absorption, synaptic growth and maturation, and the BBB. Notably, gliotransmission—the process by which astrocytes alter neuronal and synaptic function by releasing neuroactive chemicals like glutamate, ATP, and GABA [ 95 ]—was discovered to be the mechanism by which astrocytes act.…”
Section: Astrocyte–neuron Interactionsmentioning
confidence: 99%
“…Products of L-arginine metabolism represent a wide range of biologically active intermediates that participate in several metabolic and signaling pathways [ 26 - 29 ]. L-arginine metabolism products like as agmatine and polyamines (spermine, spermidine, and putrescine) are implicated in neuroprotection pathways [ 26 , 27 , 30 ]. The PRO-10c (<ENWPHPQIPP) enhances the generation of L-arginine by regulating AsS activity and expression [ 21 , 31 ] and it displays neuroprotective action in neuronal SH-SY5Y cells against H 2 O 2 -induced oxidative damage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, apart from their influence on nucleic acids metabolism, some of their actions on the neurons are known to be related to the regulation of different cation channels such as the N-methyl D-aspartate (NMDA)-type and α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) glutamate receptors [2,3], the nicotinic acetylcholine receptor [4], inward rectifier K + channels [5], or acid sensing ion channels [6]. Alterations in the neural polyamine system are involved in several brain pathological conditions such as ischemic injury, Alzheimer's disease, brain tumors, and various types of mental disorders [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%